Massively parallel analysis of human 3′ UTRs reveals that AU-rich element length and registration predict mRNA destabilization. Issue 1 (29th November 2021) - Siegel, David A; Le Tonqueze, Olivier; Biton, Anne; Zaitlen, Noah; Erle, David J
Abstract: AU-rich elements (AREs) are 3′ UTR cis-regulatory elements that regulate the stability of mRNAs. Consensus ARE motifs have been determined, but little is known about how differences in 3′ UTR sequences that conform to these motifs affect their function. Here, we use functional annotation of sequences from 3′ UTRs (fast-UTR), a massively parallel reporter assay (MPRA), to investigate the effects of 41, 288 3′ UTR sequence fragments from 4653 transcripts on gene expression and mRNA stability in Jurkat and Beas2B cells. Our analyses demonstrate that the length of an ARE and its registration (the first and last nucleotides of the repeating ARE motif) have significant effects on gene expression and stability. Based on this finding, we propose improved ARE classification and concomitant methods to categorize and predict the effect of AREs on gene expression and stability. Finally, to investigate the advantages of our general experimental design we examine other motifs including constitutive decay elements (CDEs), where we show that the length of the CDE stem-loop has a significant impact on steady-state expression and mRNA stability. We conclude that fast-UTR, in conjunction with our analytical approach, can produce improved yet simple sequence-based rules for predicting the activity of human 3′ UTRs.